ERS International Congress, Madrid, 2019: highlights from the Basic and Translational Science Assembly. Issue 1 (2nd March 2020) - Ubags, Niki D.; Baker, Jonathan; Boots, Agnes; Costa, Rita; El-Merhie, Natalia; Fabre, Aurélie; Faiz, Alen; Heijink, Irene H.; Hiemstra, Pieter S.; Lehmann, Mareike; Meiners, Silke; Rolandsson Enes, Sara; et al.
In this review, the Basic and Translational Sciences Assembly of the European Respiratory Society (ERS) provides an overview of the 2019 ERS International Congress highlights. In particular, we discuss how the novel and very promising technology of single cell sequencing has led to the development of a comprehensive map of the human lung, the lung cell atlas, including the discovery of novel cell types and new insights into cellular trajectories in lung health and disease. Further, we summarise recent insights in the field of respiratory infections, which can aid in a better understanding of the molecular mechanisms underlying these infections in order to develop novel vaccines and improved treatment options. Novel concepts delineating the early origins of lung disease are focused on the effects of pre- and post-natal exposures on neonatal lung development and long-term lung health. Moreover, we discuss how these early life exposures can affect the lung microbiome and respiratory infections. In addition, the importance of metabolomics and mitochondrial function analysis to subphenotype chronic lung disease patients according to their metabolic program is described. Finally, basic and translational respiratory science is rapidly moving forward and this will be beneficial for an advanced molecular understanding of the mechanisms underlying a variety of lung diseases. In the long-term this will aid in the development of novel therapeutic targeting strategies in the field of respiratory medicine. Highlights of basic and translational science presented at #ERSCongress 2019 summarising latest research on the lung cell atlas, lung infections, early origins of lung disease and the importance of metabolic alterations in the lung http://bit.ly/2UbdBs4